A structured laughter yoga therapy program on patients with chemotherapy-induced nausea and vomiting: A randomized clinical trial - Namazinia, Mohammad; Mazlum, Seyyed Reza; Mohajer, Samira; Lim, Khatijah Abdullah *; Salehian, Maryam (Elsevier, 2024)
Objetive Chemotherapy is a prevalent cancer treatment, often accompanied by debilitating side effects such as nausea and vomiting. This study explores the potential effectiveness of laughter yoga, a combination of exercise and voluntary laughter, in alleviating chemotherapy-induced nausea and vomiting.